Critical Thinking in Infrastructure Management: A Problem Based Learning Approach - Heri Pratikto; Madziatul Churiyah; Elvira Nur Azizah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
The growth of industrial revolution 5.0 technology provides opportunities for innovation in technology-based learning models to improve critical thinking skills. The purpose of this research is to improve critical thinking skills and student learning outcomes at Al-Islahiyah integrated vocational school through the application of the problem-based learning model with the help of Genially media. This research involved classroom action research, which was carried out for two cycles, the research subjects were class of office management automation students. The data were obtained through observation, interviews, tests, documentation, and field notes. Data analysis consists of data reduction, data presentation, and drawing conclusions. The results of this research showed that the application of the problem-based learning model with the help of the media can significantly improve student’s critical thinking skills and learning outcomes, as well as learning activities according to the steps of problem-based Learning. Keywords: Problem-based learning, Genially, Critical thinking, Learning outcomes